VMware vSphere 4 administration : instant reference - Lowe, Scott, 1970- (Serious skills., 2010)
"Get all your solutions about VMware's newest virtualization infrastructure software on the spot with this handy reference guide. Designed for quick access with special headings, thumb tabs, easy-to-read lists, and more, this book is the perfect companion to any comprehensive VMware guide, such as Mastering VMware vSphere 4"--Resource description page.